The sensuous geographies of slow art in practice: a counter-narrative to the accelerated tempo of contemporary living through art jewellery praxis - Schoeman, Jane (Stellenbosch : Stellenbosch University, 2025)
Thesis MA (VA)--Stellenbosch University, 2025.